PENGARUH KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI DI BAGIAN SOSIAL SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Hariyansyah . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Development of human resources is not the easy one to do, because its process includes all elements of organization namely: employee, leader and the system it self. The combination of those three will emerge a condusive work environment, so it will makes possible for both employee and leader able to carry out their maximum work. A condusive work environment expected to creates work satisfaction. Then, work satisfaction it self has a big influence to organization productivity whether directly or indirectly. The enhancement of employee’s work satisfaction will never be released from the role of the leader, because leadership is the main key in survival and management of organization.